SAWER SUNDA DALAM PERSPEKTIF FUSI HORIZON STUDI HERMENEUTIKA GADAMER - Ahmad Maki Maki (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2026)
Sawer Sunda is a form of oral literature that persists as a functional element in various traditional rites, particularly marriage ceremonies. This tradition serves not only as a ritual supplement but also as a medium for transmitting moral, social, and religious values within Sundanese society. This study aims to examine the meaning of Sawer Sunda as a cultural text and to explain how Islamic values interact with local traditions to shape the identity of the Sundanese Muslim community.Using a qualitative approach, the research employs text analysis and Hans-Georg Gadamer’s hermeneutics, specifically the concept of the fusion of horizons. The research data consists of sawer texts collected from wedding ceremonies and written documentation, which were then analyzed through thematic grouping and interpretative reading.The results indicate that Sawer Sunda functions as a living tradition embodying educational, social, and religious roles. The meaning of sawer is not static; rather, it is formed through a dialogue between the